Opening the black box: Unpacking board involvement in innovation. (November 2020) - Klarner, Patricia; Probst, Gilbert; Useem, Michael
Corporate governance research suggests that boards of directors play key roles in governing company strategy. Although qualitative research has examined board–management relationships to describe board involvement in strategy, we lack detailed insights into how directors engage with organizational members for governing a complex and long-term issue such as product innovation. Our multiple-case study of four listed pharmaceutical firms reveals a sequential process of board involvement: Directors with deep expertise govern scientific innovation, followed by the full board's involvement in its strategic aspects. The nature of director involvement varies across board levels in terms of the direction (proactive or reactive), timing (regular or spontaneous), and the extent of formality of exchanges between directors and organizational members. Our study contributes to corporate governance research by introducing the concept of board behavioral diversity and by theorizing about the multilevel, structural, and temporal dimensions of board behavior and its relational characteristics.